Hierarchical Optimization of Voltages, VArs and Real Power in Distribution Networks - Su, Xiangjing (Curtin University, 2015)
This PhD research proposes a multi-objective hierarchical optimization strategy to improve the operational and computational performance of complex distribution networks in smart grid era. By coordinating the PV inverter controllers of unbalanced four-wire LV distribution feeders and the delta switched capacitor controller of unbalanced three-wire MV distribution network, the proposed hierarchical strategy could effectively and efficiently exploit the capabilities of both conventional and emerging devices, expand the network load capacity and accommodate more renewable connections.